2002
DOI: 10.1002/cncr.10999
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term cognitive outcome, brain computed tomography scan, and magnetic resonance imaging in children cured for acute lymphoblastic leukemia

Abstract: Erwarte das Unerwartete: Die Reaktion von Imidazoliumpyridinium‐Salzen mit [{IrCp*Cl2}2] und [{RhCp*Cl2}2] lieferte eine Serie von Komplexen. Neben den erwarteten Bis(NHC)‐Komplexen wurden auch Spezies beobachtet, die aus der C‐C‐Kupplung zwischen den Pyridyliden‐ und den Cp*‐Liganden hervorgehen (siehe Schema; Cp*=Pentamethylcyclopentadienyl).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
61
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 40 publications
5
61
1
4
Order By: Relevance
“…These fi ndings are in accordance with those of previous studies in adults with brain tumours who have had radiotherapy 9,10 and in children who have had radiotherapy. 12,13 The results of previous studies have suggested that a high fraction dose might account for the cognitive defi cits in patients after radiotherapy. 14,16 However, the results presented here indicate that all surviving patients who had radiotherapy are at risk of developing attentional problems at some point.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These fi ndings are in accordance with those of previous studies in adults with brain tumours who have had radiotherapy 9,10 and in children who have had radiotherapy. 12,13 The results of previous studies have suggested that a high fraction dose might account for the cognitive defi cits in patients after radiotherapy. 14,16 However, the results presented here indicate that all surviving patients who had radiotherapy are at risk of developing attentional problems at some point.…”
Section: Discussionmentioning
confidence: 99%
“…Radiologically detectable brain abnormalities (eg, white matter hyperintensities and brain atrophy) have consistently been found to a greater extent among patients who had radiotherapy than among those who did not, [7][8][9][10][11] and these radiological abnormalities are associated with poor cognitive performance. 9,10,12,13 Because whole-brain radiotherapy is associated with cognitive defi cits, 9,14,15 focal radiotherapy has been the preferred treatment for LGG for the past decade. However, the eff ects on cognition of local radiotherapy in long-term survivors of LGG have not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…Risk factors identified from studies of patients with acute lymphoblastic leukemia and brain tumors include young age at treatment [13,23,3,1], dose and type of treatment, particularly cranial irradiation and high-dose chemotherapy [13,15,25], increased time since treatment [26,23], and female gender [3]. Structural changes, including subacute leukoencephalopathy, mineralizing microangiopathy, and cortical atrophy, have been observed on CT or MRI during and after treatment [5], but associations between NP deficits and structural abnormalities are inconsistent and yield mixed results [18,28]. Early detection and improved objective characterization of NT would be useful in the clinical management of these patients.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Some revealed damage as global deficits in the form of lower intelligence test scores, while others showed specific attention and memory deficits. [9][10][11] Cranial RT as well as intrathecal chemotherapy results in these complications. [12][13][14][15] Comparison of the effects of various therapeutic approaches has resulted in reduction in the neurotoxicity of various regimens.…”
Section: Introductionmentioning
confidence: 99%